2017
DOI: 10.1128/jvi.01934-16
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Low-Pathogenic Avian H7 Influenza A Viruses To Replicate and Cause Disease in a Mammalian Model

Abstract: H7 subtype influenza A viruses are widely distributed and have been responsible for human infections and numerous outbreaks in poultry with significant impact. Despite this, the disease-causing potential of the precursor low-pathogenic (LP) H7 viruses from the wild bird reservoir has not been investigated. Our objective was to assess the disease-causing potential of 30 LP H7 viruses isolated from wild avian species in the United States and Canada using the DBA/2J mouse model. Without prior mammalian adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Laboratory studies have shown only three amino acids are required to completely change receptor specificity from avian to human, allowing human-to-human transmission and increasing the chance of a new pandemic (8). In fact, an outbreak of H7N9 virus in China in 2013 has been linked to close contact of humans with poultry where chickens, ducks, and pigeons were identified as a reservoir for the virus (7,9). Since then, H7N9 has continued to circulate in poultry reservoirs causing a spike in human infections in recent years (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have shown only three amino acids are required to completely change receptor specificity from avian to human, allowing human-to-human transmission and increasing the chance of a new pandemic (8). In fact, an outbreak of H7N9 virus in China in 2013 has been linked to close contact of humans with poultry where chickens, ducks, and pigeons were identified as a reservoir for the virus (7,9). Since then, H7N9 has continued to circulate in poultry reservoirs causing a spike in human infections in recent years (7).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, an outbreak of H7N9 virus in China in 2013 has been linked to close contact of humans with poultry where chickens, ducks, and pigeons were identified as a reservoir for the virus (7,9). Since then, H7N9 has continued to circulate in poultry reservoirs causing a spike in human infections in recent years (7). Several H7-specific mAbs have been described recently, including H7.137, H7.167, and H7.169, which target highly conserved regions of the HA head adjacent to the RBS (10).…”
Section: Introductionmentioning
confidence: 99%
“…Although all of H7Nx subtypes have been isolated from wild birds, H7N1 [ 50 ], H7N3 [ 51 ], and H7N7 [ 52 ] subtypes have shown high pathogenicity to poultries. Recent studies demonstrated that many LPAI H7 viruses isolated from avian species in Eurasia and North America caused mortality in mice prior to adaptation [ 53 54 55 ], suggesting a potential public health risk. Furthermore, various avian H7 subtypes in combination with N2, N3, N7, and N9 have been introduced into humans through exposure to domestic poultry [ 7 ].…”
Section: Adaptation Using Avian Influenza Viruses In Micementioning
confidence: 99%
“…Like HPAI H5N1, many H7 viruses, including LPAIs, are lethal to mice prior to adaptation [ 53 ]; many studies have demonstrated the adaptation of both HPAI [ 57 58 ] and LPAI [ 59 60 ] H7 viruses in mice to identify genetic determinants of virulence in a mammalian host. Both HPAI and LPAI H7 viruses acquired high virulence in three to seven passages in mice lungs [ 57 59 60 ]; this is slower than HPAI H5N1, but faster than LPAI H5N2 viruses.…”
Section: Adaptation Using Avian Influenza Viruses In Micementioning
confidence: 99%
“…Viruses isolated from human cases, perhaps including secondary cases of human transmissions, show only a few accumulated mutations in surface glycoproteins ( 2 ). Thus, it is difficult to predict the antigenic determinants of transmissibility that are needed to break the zoonotic barrier and also how these would influence the viral pathogenicity in humans ( 3 ). However, the human population is presently serologically naive toward H7 influenza; therefore, the potential acquisition of mutations enabling efficient human-to-human transmission could have a devastating effect.…”
Section: Introductionmentioning
confidence: 99%